(3GdfMd hGdedds - (3Ydj Hf CMeO Hf SYjO Hf MRe GdXGgQj, GHf MRe , CHh eMeO ,J (B456 (3g` s
(3ChdgG (B:s
(3GdcdGe gd TGA Gddg YR hLd chf GdcaQ hGdaSb hCQGO hbhYg Ce de jTC JYGdi chfg hdG CQGOg s
(3BNQgG (B:s
(3bGd CHh eMeO (B: (3bO GfJgi cdGefG ai OjhGffG gPG ceG hLOfG hGdMeO ddg QH GdYGdejf GdeYjf Ydi Pdc hfSCdg Cf jLYdg dPGJg , hCf jUdi Ydi YHOg hQShdg eMeO NGJe CfHjGFg hYdi Bdg hSde s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B254 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B17 - (3U (B16s
Keywords: (3GdJhMjO hGdedd hGdfMds